Impact of protective agents and drying methods on desiccation tolerance of Salix nigra L. seeds - Santagapita, Patricio Roman (2014)
Willow seeds are classified as orthodox, but they show some recalcitrant characteristics, as they lose viability in a few weeks at room temperature. The aim of this work was to improve the desiccation tolerance of willow seeds (Salix nigra L.), as a model of sensitive materials to dehydration, through imbibition in solutions and later vacuum (VD) or freeze-drying (FD). Imbibition was conducted with 45% w/v trehalose or polyethylene glycol 400 -PEG- or water prior to dehydration treatments. Water- and especially trehalose-imbibed seeds subjected to VD showed better germination capability with respect to the freeze-dried ones. Water crystallization was mainly responsible for the great loss of capability germination observed in water- or trehalose-imbibed seeds subjected to FD. PEG behavior was better when seeds were FD instead of VD. DSC thermograms of seeds allowed to identify two thermal transitions corresponding to lipids melting and to proteins denaturation. This last transition reveals information about proteins state/functionality. Dehydration of control and PEG- or water-imbibed seeds affected proteins functionality leading to lower germinability. In the case of trehalose-imbibed seeds subjected to VD, proteins maintained their native state along dehydration, and the seeds showed a great germination capacity for all the water content range. Germinated seeds showed higher luminosity (L*), greenness (a*) and yellowness (b*) values than not-germinated seeds independently of the employed agent. Present work reveals that the presence of adequate protective agents as well the dehydration method were the main critical factors involved in willow seed desiccation tolerance.